2008
DOI: 10.1021/jo801337k
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Nitrile Oxides under Nanometer Micelles Built in Neutral Aqueous Media: Synthesis of Novel Glycal-Based Chiral Synthons and Optically Pure 2,8-Dioxabicyclo[4.4.0]decene Core

Abstract: A highly efficient strategy for chemoselective oxidation of aldoximes to nitrile oxides by iodosobenzene in neutral aqueous media is reported. Their in situ intermolecular 1,3-dipolar cycloaddition (1,3-DC) with olefins in nanometer aqueous micelles occurs with improved stereoselectivity and acceleration of reaction rate toward synthesis of new chiral synthons, 3-(2'-C-3',4',6'-tri-O-benzylglycal)-Delta(2)-isoxazolines and others. Construction of optically pure 2,8-dioxabicyclo[4.4.0]decene skeleta is performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(26 citation statements)
references
References 52 publications
1
25
0
Order By: Relevance
“…In fact, we have reported 1,3‐dipolar cycloaddition of nitrile imines generated from araldehyde phenylhydrazones in the presence of chloramine‐T to activated olefins to synthesize pyrazolines . From the literature, it was observed that iodosobenzene not only serves as a source of oxygen in various metal‐catalyzed oxidation reactions but also oxidizes aldoximes to nitrile oxides and in the presence of cationic surfactant cetyltrimethylammonium bromide (CTAB) the reaction proceeded well . However, there are sparce reports to generate nitrile imines from araldehyde phenylhydrazones in the presence of iodosobenzene and CTAB.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, we have reported 1,3‐dipolar cycloaddition of nitrile imines generated from araldehyde phenylhydrazones in the presence of chloramine‐T to activated olefins to synthesize pyrazolines . From the literature, it was observed that iodosobenzene not only serves as a source of oxygen in various metal‐catalyzed oxidation reactions but also oxidizes aldoximes to nitrile oxides and in the presence of cationic surfactant cetyltrimethylammonium bromide (CTAB) the reaction proceeded well . However, there are sparce reports to generate nitrile imines from araldehyde phenylhydrazones in the presence of iodosobenzene and CTAB.…”
Section: Resultsmentioning
confidence: 99%
“…The isoxazoline ring is present in many important heterocycles that are widely used in several areas of chemistry and biomedical sciences. [24][25][26]52 Hypervalent iodine reagents such as (diacetoxyiodo)benzene, [115][116][117][118][119][120][121][122][123][124][125][126][127][128][129] [hydroxy(tosyloxy)iodo]benzene, 130,131 iodosylbenzene, [132][133][134][135] [bis(trifluoroacetoxy)iodo]benzene, 136 (dichloroiodo)benzene, 137 and also in situ generated iodine(III) species, [138][139][140][141] can be used as efficient tools for construction of the isoxazoline ring.…”
Section: Scheme 17 Metal-free [2+2+1] Oxidative Cycloaddition Reactiomentioning
confidence: 99%
“…The hypervalent-iodine-mediated oxidative cycloaddition of aldoximes with unsaturated substrates represents a powerful methodology for the synthesis of isoxazoline compounds. 52,[115][116][117][118][119][120][132][133][134]136,137 For example, the reactions of various aldoximes 54 with alkenes 55 and (diacetoxyiodo)benzene afford the corresponding isoxazolines 56 in generally high yields (Scheme 18). 116 The key intermediate in this reaction, nitrile oxide, is generated by oxidation of the aldoxime with (diacetoxyiodo)benzene, and then the generated nitrile oxide reacts with alkenes to produce the isoxazoline products.…”
Section: Scheme 17 Metal-free [2+2+1] Oxidative Cycloaddition Reactiomentioning
confidence: 99%
“…The INOC reaction of 2-allyloxybenzaldoximes and sugar-derived aldoximes using hypervalent iodine(III) reagents selectively affords the respective ring fused isoxazoline products. [47][48][49][50] In particular, Yao and co-workers have demonstrated that the INOC reaction of 2-allyloxybenzaldoximes 26 using Koser's reagent in water gives the corresponding tricyclic isoxazoline derivatives 27 in moderate to good yields (Scheme 7). 49 This is an environmentally friendly reaction, which can be easily handled in water without special care.…”
Section: Cycloaddition Of Aldoximes Leading To Isoxazolinesmentioning
confidence: 99%